PENGARUH STRUKTUR KEPEMILIKAN TERHADAP PENGUNGKAPAN PERTANGGUNGJAWABAN SOSIAL (CSR DISCLOSURE) DALAM LAPORAN TAHUNAN PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) - B41108100, DEVI RIANTI SARI (Jurnal KIAFE, 2012)
This study aimed to determine the effect of ownership structure with a proxy of foreign ownership and institutional ownership and firm size categories of BUMN and non-BUMN as control variables to make the approach to the disclosure of corporate social responsibility within the sample. This study is an econometric study uses empirical data to sample the mining company listed on the Indonesia Stock Exchange (IDX). The sample used by 8 companies with a total of 24 companies in the observation period of 3 years between 2008 and 2010 based on purposive sampling. Thus, the data used is panel data. The analysis method used is multiple regression. To test this hypothesis, using t-test statistics and test of determination. Determination test shows R-squared value of 0.902079. This means that 90.2% of social responsibility disclosure can be explained by the foreign ownership, institutional ownership, firm size and category of BUMN and non-BUMN. Based on the t test, it was found that all variables are highly significant positive effect on the disclosure of social responsibility by the coefficient of each variable is for foreign ownership of 0.0077, 0.0090 for institutional ownership, firm size at 0.0000, and the category of BUMN and non-BUMN of 0.0001 with a significance level of 5%. Keywords: social responsibility disclosure, foreign ownership, institutional ownership, firm size, category BUMN and Non-BUMN